Lawyer's liability (Research, Society and Development, 2023)
In this article, compliance with the relevant legislation is analyzed regarding the correct performance of the lawyer in the provision of his services, his ethical performance and the civil liability attributed to him, which consists of the duty that the lawyer has to indemnify his contractor for acts performed within the process. In short, there is irresponsibility in the area of ​​law, an issue that has been negatively affecting people's lives for a long time and is increasingly becoming more present, considering that these errors can lead to the loss of a chance for the contractor. mistakes, can end up becoming part of everyday life if no measure is adopted to solve such a problem, there are measures and mainly care that a professional in the area of ​​law must take, so that this type of situation does not occur under any circumstances, simple actions , but which can change the course of a case. But when mistakes are made, there is legislation to take care of these cases, if they suffer punishment, they can go from the simplest to the most severe, different degrees in different situations, thus showing that justice is for everyone.